OPTIMALISASI EDUKASI SELF CARE MANAJEMENT HIPERTENSI MELALUI BUKU KONTROL PADA KELUARGA Tn. A DENGAN ANGGOTA KELUARGA PENDERITA HIPERTENSI DI WILAYAH KERJA UPT PUSKESMAS SINGKAWANG UTARA 2 TAHUN 2023 - wati, ira (Scientific Journal of Nursing Research, 2024)
Background: Hypertension is called a silent killer because it is often without symptoms but is later diagnosed after having complications. Comprehensive approaches and family support are needed to change healthy lifestyle behaviors for hypertensive patients through self-care management education. Purpose of writing: The aim of this study is to determine the effectiveness of family nursing care for hypertension and self-care management education through pocket books. General overview of administrative cases: The respondent to this nursing care is the family of Mr. A, who has hypertension in the work area of UPT Puskesmas Singkawang North 2 Year 2023. Data is collected through the family assessment format for subsequent nursing up to the evaluation stage. EBNP application results: When the evaluation obtained the pre-test and post-test results of health education education, which are the pre-test value of 33 and post-test value of 83, in addition to the fact that blood pressure decreased from 180/110 mmHg at the first visit to 143/79 mmHg after the third visit, there was also a change in behavior where families are willing to follow Posbindu to control blood pressure. Conclusion: The conclusion of nursing care is that giving education on self-care management of hypertension with pocket books is considered effective in improving knowledge of self-care management in the family and improving healthy life behaviors so that blood pressure becomes better controlled. Recommendation: Self-care management in hypertensive patients is very important to be done so that patients can improve satisfaction in life, reduce the cost of treatment, increase confidence and independence, and improve their quality of life.